Aplicabilidade dos produtos resultantes dos mestrados profissionais da UFRR, no período de 2019 a 2021 - Morais, Ana Patrícia (Universidade Federal de Roraima, 2023)
This study is the result of an investigation into the Applicability of the products resulting from the UFRR Professional Masters, from 2019 to 2021. In this sense, the objective was to map the applicability of the technical and/or technological productions and educational processes/products of the six Education Programs. UFRR Professional Post-Graduation, through the courses offered: PROCISA, PROFMAT, MNPEF, PROFNIT, PROFÁGUA and PROFHISTÓRIA. It is about knowing the contribution of the products of these masters to institutions and companies in the local and national scenario. Therefore, this research carried out a quantitative and descriptive cross-sectional approach, in which bibliographical and documental research was used necessary to carry out the mapping, identify and describe these productions. 87 questionnaires were sent via e-mail to graduates of the said master's degrees, with the return of 47 questionnaires answered, in order to know the types of products; relationship with technology and education; products with trademark, patent and industrial design registrations and their applicability. Among the 137 products developed by graduates and collected in the survey, the most frequent resulting from master's degrees are: scientific article; educational and informative folders; thematic maps; technical reports, guides, booklets, didactic sequences and proposals for innovative programs and other products in different formats. The results also indicated that in some masters there is applicability of the products in local and national environment, while others did not present positive data in this sense. The research proves to be relevant in the sense of providing knowledge about the effectiveness of the offer of products from the Professional Postgraduate Course at UFRR, for its practical use for institutions in the local and national scenario, and may also serve as a basis, for its results, in the evaluation and planning processes of professional master's degrees. Because it is a pioneering research at the institution, it provides relevant data, which allow an understanding of the dynamics of the institution's production. It is hoped that the study will contribute to the institutional actions of promotion and dissemination of the technical and educational production of the Professional Graduate Studies at UFRR.